PENINGKATAN LUAS PERMUKAAN KONVERTER RADIASI MATAHARI UNTUK MENINGKATKAN TEMPERATUR DAN DAYA LISTRIK YANG DIHASILKAN OLEH SISTEM GENERATOR TERMOLISTRIK - Selestina Yulita Merit Bame; Ishak Semuel Erari; Abdul Muis Muslimin; Sangaji Hasmi Maharani Ipa (Jurnal Natural, 2022)
The development of the use of solar energy as a new renewable energy is being encouraged in various forms of its use, and one of them is the conversion of solar energy into electrical energy. The Thermoelectric Generator (TEG) module is a power generation system that utilizes temperature differences to produce electric power. The temperature difference can be obtained from solar radiation the metal will convert into heat energy, which will pass through the TEG and be discharged into the environment. The amount of solar radiation converted into heat depends on the area of ​​the converter. This research aim is to increase the surface area of ​​the solar converter to increase the temperature used in the TEG system to generate electric power. The areas used for capturing solar radiation are 0.06 m2, 0.12 m2 and 0.16 m2 which are made of black aluminum plates in a closed system. At the bottom of the aluminum are installed 7 thermoelectric modules connected to a water reservoir as a coolant. The results of the study showed that the highest temperatures that could be achieved were respectively 39.1, 52.5 and 61oC, and the temperature differences that could be achieved were respectively 9.1; 20.0 and 28 oC. A temperature difference of 7.1 oC produces an electric power of 64.2 mW, and a temperature difference of 28 oC produces an electric power of 282.8 mW.